Hadith #4889 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Ibrahim bin Nshyt إبراهيم بن نشيط; Ka'b bin 'Alqama bin Ka'b كعب بن علقمة بن كعب; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Uqba bin 'Amir al-Juhayni (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a ruler seeks to make imputations against the people, he corrupts them.
Grade: Sahih

Hadith #4890 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Ibrahim bin Nshyt إبراهيم بن نشيط; Ka'b bin 'Alqama bin Ka'b كعب بن علقمة بن كعب; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan Abi Dawud)
Zayd ibn Wahb said: A man was brought to Ibn Mas’ud. He was told: This is so and so, and wine was dropping from his beard. Abdullah thereupon said: We have been prohibited to seek out (faults). If anything becomes manifest to us, we shall seize it.
Grade: Sahih